Rice Morphogenesis and Chlorophyll Accumulation Is Regulated by the Protein Encoded by NRL3 and Its Interaction With NAL9 - Chen, Wei; Sheng, Zhonghua; Cai, Yicong; Li, Qianlong; Wei, Xiangjin; Xie, Lihong; Jiao, Guiai; Shao, Gaoneng; Tang, Shaoqing; Wang, Jianlong; Hu, Peisong (Frontiers in Plant Science, 2019)
Rice yield is closely related to plant leaf shape and chlorophyll content. In this study, we isolated and identified a narrow and rolled leaf mutant, temporarily named nrl3, with darker green leaves. Histological analysis showed that nrl3 has a reduced number of vascular bundles and undergoes abnormal abaxial sclerenchymatous cell differentiation. The NRL3 mutant phenotype is controlled by a single recessive gene, fine-mapped to a 221 kb interval between Indel3 and RM2322 on Chr3. There are 42 ORF in this interval. Sequencing identified an SNP mutant leading to a premature stop in ORF 18, the candidate gene. Bioinformation analysis indicated that NRL3 encodes a novel protein with unknown function. NRL3 is localized in cytoplasm, membrane and nucleus. Expression analysis of nrl3 showed that genes involved in chlorophyll synthesis were significantly up-regulated while those involved in chlorophyll degradation and programmed cell death (PCD) were significantly down-regulated. The expression levels of photosynthesis genes were also affected. Y2H and BIFC assays indicated that NRL3 interacts directly with NAL9/VYL to regulate leaf morphology in rice. Thus, NRL3 plays an important role in leaf morphogenesis and chlorophyll accumulation, and can be used as a new gene resource for constructing improved rice.